2022
DOI: 10.1371/journal.pone.0275976
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on implementation of mass testing, treatment and tracking of malaria in rural communities in Ghana: A qualitative study

Abstract: Background Mass test, treat and track (MTTT) of malaria is ongoing in the Pakro sub district of Ghana. In the delivery of MTTT of malaria, community health volunteers are trained to routinely provide this service through a door-to-door strategy. Following the report of the first cases of COVID-19 in Ghana, we conducted this study to explore the effects of the pandemic on the implementation of the MTTT of malaria intervention. Methods Using qualitative methodology, we conducted ten focus groups discussions (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…For northern Ghana, a retrospective analysis of quantitative data from April to September 2020 compared to the pre-COVID-19 period from 2015 to 2019 found a 26% decrease in overall OPD malaria cases with even stronger reductions in children under the age of five and inpatients (up to 67%) [ 20 ]. Similar findings were seen in other regions of Ghana, as investigated in a qualitative study in a rural community in the Eastern Region [ 21 ] and in a quantitative study in the Volta Region [ 22 ]. Verner et al [ 22 ] further reported an increase in cerebral malaria, resulting in shorter admission durations and followed by a higher malaria related mortality in 2020, compared to the years 2016–2019.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…For northern Ghana, a retrospective analysis of quantitative data from April to September 2020 compared to the pre-COVID-19 period from 2015 to 2019 found a 26% decrease in overall OPD malaria cases with even stronger reductions in children under the age of five and inpatients (up to 67%) [ 20 ]. Similar findings were seen in other regions of Ghana, as investigated in a qualitative study in a rural community in the Eastern Region [ 21 ] and in a quantitative study in the Volta Region [ 22 ]. Verner et al [ 22 ] further reported an increase in cerebral malaria, resulting in shorter admission durations and followed by a higher malaria related mortality in 2020, compared to the years 2016–2019.…”
Section: Introductionsupporting
confidence: 86%
“…Overlapping symptoms of malaria and COVID-19 reduced the health facility attendance and changed the treatment behaviour of HCPs, HCPs were stigmatised as infection sources, and misinformation about COVID-19 vaccinations and testing affected the participation in malaria prevention programmes. [ 21 ] Amu et al [ 33 ] set the focus in their research on health system functioning in SSA, supporting the result of limited financial resources in health facilities, leading to following result: “…the majority of the population in SSA still suffer financial barriers as out-of-pocket expenditure is required before essential medical care can be delivered, even in emergencies. In such situations, the most vulnerable (poor), therefore, bear the highest burden of diseases and high levels of health expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the COVID-19 pandemic has posed an overwhelming burden on the fragile healthcare systems in Africa and has disrupted various health-care services, including malaria prevention and treatment programs [ 20 ]. The COVID-19 pandemic has adversely affected the provision and uptake of malaria prevention and treatment services, especially the mass test, treat and track (MTTT) of malaria being implemented at the community level in Ghana [ 21 ]. The civil conflict and lack of healthcare services present compounded with the COVID-19 pandemic resulted in a five- to tenfold increase of malarial incidence in the past years in Afghanistan [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that this treatment-seeking was due to COVID-19 since the majority, 91.6%, had no history of COVID-19 in the last one month. Outpatient data collected during the COVID-19 epidemics in Ghana showed that treatment-seeking due to malaria increased in communities in the south 8 compared to the north 3 . This uptick in treatment-seeking happened post-lockdowns and following rollout of COVID-19 vaccinations in early 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, significant overlaps in the clinical presentations and epidemiological distribution of malaria, caused by Plasmodium falciparum , and COVID-19 cases in endemic communities in Ghana have contributed to malaria misdiagnosis and impacted the effectiveness of interventions 7 . While uptake of interventions at the community level declined during the COVID-19 disruptions 8 , there is limited data to assess malaria case and co-infection rates in communities with active SARS-CoV-2 transmission.…”
Section: Introductionmentioning
confidence: 99%